(untitled) (Linguostylistic Studies, 2022)
This article highlights typical structural-semantic organization components of the President of Poland Andrzej Duda’s ceremonial speeches. The study focuses on the traditional models of ceremonial speeches, the core compositional elements of which are the introduction, the central part, and the conclusion, and the language features relevant to those mandatory components of solemn speeches. The study has revealed that solemn texts have a clear structural organization determined by the genre’s tradition. However, we are currently observing a trend towards some transformations in the discourse content and increasing the share of emotional and expressive means of influence. The actualization of the micro-topic of Ukraine in the speeches of the President of Poland from February 2022 can be considered typical as a demonstration of international support and a desire to help the neighboring state to defend European values and defeat the enemy. Obligatory components of solemn congratulation speeches are address, congratulatory and stating parts, and wishes. The final part of the speech mainly contains a reminder of the festive event and a repeated component of the greeting, forming a kind of framing of the text. The author argues that the structural-semantic organization of the President’s of Poland ceremonial speeches is mainly determined by the specifics of the events at which they are delivered and by the functional characteristics. Mostly during charity events and religious holidays, A. Duda makes public appearances together with his wife, who is, traditionally, the first to address the audience. This approach emphasizes firmly-promoted values of Polish society, one of which is the family. Innovative for political discourse is the speech-dialogue on the occasion of Easter, which is structured as an alternate exchange of lines between the presidential couple.